Leading Polish missionary journals during the Covid-19 pandemic, their functioning, message and realization of press functions - Wrzos, Marcin (Studia Theologica Varsaviensia, 2022)
This research has confirmed the need for missionary periodicals on the Polish press market, which have specific tasks and functions to perform. Declining circulation should lead to some consolidation of press titles and to cooperation and raising the standard of individual titles. The period of the pandemic proved that the leading Polish missionary periodicals react quickly to the crisis situation, provide reliable and wide-ranging information about it, and in some titles this translates into an invitation to readers to commit themselves spiritually and materially to specific needs. From the course of the analyses carried out, we can verify the hypotheses or confirm the theses posed before the research began. Thesis 1. During the Covid-19 pandemic, the leading missionary journals carried out the press functions for which they were established - confirmed, although mainly in terms of information-publicity, fundraising and organising functions. Thesis 2. During the Covid-19 pandemic, the leading missionary magazines reported on the pandemic situation in mission areas and publicised the social campaigns that were being conducted - confirmed, although some titles more than others. Hypothesis 1. There is a deepening crisis of missionary journalism, in favour of missionary media communicating via the internet. It seems necessary to adapt different content to the two distinct target groups (audiences) - verified positively. Hypothesis 2. There is a need for change and centralisation on the market of missionary journalism - verified positively.